The Latest Evolution in Virtual Surgical Planning: Customized Reconstruction Plates in Free Fibula Flap Mandibular Reconstruction. Issue 4 (October 2020) - Lee, Z-Hye; Alfonso, Allyson R.; Ramly, Elie P.; Kantar, Rami S.; Yu, Jason W.; Daar, David; Hirsch, David L.; Jacobson, Adam; Levine, Jamie P.
Abstract : Background: Virtual surgical planning has contributed to technical advancements in free fibula flap mandible reconstruction. The authors present the largest comparative study on the latest modification of this technology: the use of patient-specific, preoperatively customized reconstruction plates for fixation. Methods: A retrospective chart review was performed on all patients undergoing mandibular reconstruction with virtually planned free fibula flaps at a single institution between 2008 and 2018. Patient demographics, perioperative characteristics, and postoperative outcomes were reviewed. Reconstructions using traditional fixation methods were compared to those using prefabricated, patient-specific reconstruction plates. Results: A total of 126 patients (mean age, 48.5 ± 20.3 years; 61.1 percent male) underwent mandibular reconstruction with a free fibula flap. Mean follow-up time was 23.5 months. A customized plate was used in 43.7 percent of cases. Reconstructions with patient-specific plates had significantly shorter total operative times compared with noncustomized fixation methods (643.0 minutes versus 741.7 minutes; p = 0.001). Hardware complications occurred in 11.1 percent of patients, with a trend toward a lower rate in the customized plate group (5.5 percent versus 15.5 percent; p = 0.091). Multivariate regression showed that the use of customized plates was a significant independent predictor of fewer overall complications ( p = 0.03), shorter operative time ( p = 0.014), and shorter length of stay ( p = 0.001). Conclusions: Compared to traditional fixation methods, patient-specific plates are associated with fewer complications, shorter operative times, and reduced length of stay. The use of customized reconstruction plates increases efficiency and represents the latest technological innovation in mandibular reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.